Electrically detected magnetic resonance study on defects in Si pn‐junctions created by proton implantation. Issue 11 (8th August 2014) - Gruber, Gernot; Kirnstoetter, Stefan; Hadley, Peter; Koch, Markus; Aichinger, Thomas; Schulze, Holger; Schustereder, Werner; Pizzini, Sergio; Kissinger, Gudrun
Abstract The present study focuses on electrically detected magnetic resonance (EDMR) investigations of proton implanted silicon. The samples were prepared on n‐type silicon wafers highly doped diffused boron (B) p‐region, forming a pn‐junction. A large additional n‐type doping was introduced by proton (H+) implantation. We compare samples with implantation doses up to 1015 H+/cm–2 and investigate the effects of anneals at 350 °C. We observe different types of defects in the differently prepared samples. One doublet with 118.5 G HF splitting and a g ‐value of 2.0095(4) is only observed in the samples implanted with the highest dose and is assigned to hydrogen. The structure of the other observed defects remains unidentified and can only tentatively be assigned to hydrogen. More extensive measurements would have to be performed to get a better picture. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)